La estimulación temprana como factor principal en el desarrollo de habilidades sociales en los niños y niñas de 0 a 3 años del Centro Integral del buen vivir “Gotitas de Dulzura” de la Ciudad de Riobamba durante el periodo 2015-2016 - Mesache Miranda, Rosa Isabel (2016)
Playing is a fundamental part in the existence of children because through it explore, develop, express their feelings, emotions and desires in the surrounding environment, the support of the teacher is very necessary because this person encourages and motivates integration, for this reason it is vital that early stimulation to support the development of social skills in children aged 0 to 3 years of the ‘'Centio Integral del Buen Vivir Gotitas de Dulzura” Riobamba City Chimborazo Province. This research work emerged from a problem whose theme is early stimulation as the main factor in the development of social skills, the main objective is to analyze in depth the problem mentioned in view that there is difficult in children to socialize with others. This research is focused in one of the most frequent problems living within CIBV, and consists of the deductive method; the technique of indirect scientific observation. Direct and structured scientific observation that allowed to organize activities with the ahn of achieving a solution to the problem, also contains theoretical basis of different authors and works that are based on a set of clear, comprehensive and accurate knowledge, they helped select early stimulation activities where children actively interact in the environment around them, and are detailed in the game guide with friend and the structure of both the independent variables and the dependent discussed with concepts that facilitates analysis and understanding; it has the methodology, research design; research methods, techniques and tools; as a technical guide was used and his instrument was the evaluation of the guide, with a sample of 92 children, in the proposal step by step guide the activities undertaken described and is distributed in Children's Songs, Rounds Children and Games traditional; the presentation and discussion of results with the test in of hypotheses that superficial the importance of applying the guidance it strengthens socialization in children is presented. Finally, with the results the conclusion and recommendations were established.